High genetic variations of the stingless bee Tetragonula laeviceps based on Mitochondrial DNA of Cytochrome C oxidase Subunit 1 (CO1) gene in sumatra and Java, Indonesia - Tiara Sayusti,; Rika Raffiudin,; Tri Atmowidi,; Cahyani Nur Aisyah,; Faishal Rahman Ludiro,; Ryzka Annisa Baher,; Ramadhani Eka Putra,; RC Hidayat Soesilohadi,; Hery Purnobasuki, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The stingless bee Tetragonula laeviceps (Hymenoptera: Apidae) is frequently traded from its native regions to many areas across Indonesia for meliponiculture purposes. This species has a high morphological variation that make it difficult to identify. Identification at the molecular level based on the cytochrome c oxidase subunit 1 (COI) gene from mitochondrial DNA is needed to support morphological identification. However, there is a lack of COI gene data for these bees in the GenBank. Thus, this research aimed to characterize T. laeviceps in Indonesian native and traded regions using the CO1 gene. Stingless bee samples were collected from two native regions: Batanghari (Jambi, Sumatra) and Lebak (Banten, Java), while the traded bee colonies were from Bogor (West Java, Java). The COI gene primers were manually designed based on the complete CO1 gene of Melipona bicolor (AF466146). Twenty-four nucleotide variations from 13 individuals of T. laeviceps CO1 gene sequences were found and classified into six haplotypes (Hap_1–Hap_6). The substitution of nucleotide number 157 of T. laeviceps CO1 gene altered to a single putative amino acid from serine to phenylalanine. A high (3.7%) genetic distance was found between the Hap_1 haplotype (Batanghari and Bogor) and other haplotypes (Hap_4 and Hap_6). The Hap_1 performed a single clade split from other haplotypes with 82% bootstrap value in the phylogenetic tree, meaning that the Hap_1 of T. laeviceps presumably has a high genetic differentiation. Extensive studies using T. laeviceps from a wider distribution area are needed to explain the haplotype variation thoroughly